Unraveling the complexity of cognitive impairment following high-altitude exposure: from preclinical animal models to human organoids - Gong, Hong; Liu, Yu-Xin; Xiaoluo, Qing-Lu; Gong, Mei-Feng; Liu, Zhi; Wu, Sheng-Ru; Chen, Zhen-Yang; Liu, Tian-Yao; Zhao, Jing-Hui; Wang, Lian; Fan, Xiao-Tang; Xu, Hai-Wei (Frontiers in Neuroscience, 2025)
Long-term exposure to high-altitude hypobaric hypoxia has a detrimental effect on cognitive function. These effects are dependent on multiple factors, including altitude, exposure duration, pre-acclimatization conditions, psychological traits, and individual differences. Existing studies have investigated pathogenesis, epidemiology, and interventions for hypobaric hypoxia-associated cognitive impairment based on population studies and preclinical models. The underlying pathophysiological mechanisms involve energy metabolism, neuronal autophagy, oxidative stress, inflammatory response, gut microbiota imbalances, and genetic susceptibility. However, no consensus has been reached on the most important mechanisms and most recommended animal models, and no standard effective interventions are currently available. This review aims to provide new insights and research perspectives for cognitive impairment following high-altitude exposure. By systematically summarizing the pathophysiological mechanisms of hypobaric hypoxia-associated cognitive impairment, we comprehensively compare animal models for studying high-altitude-induced cognitive decline using three paradigms, i.e., mild, moderate, and extreme high-altitude exposure. Additionally, we introduce various in vitro models, including pluripotent stem cells and brain organoids, which can be used to evaluate the potential mechanisms and therapies. Furthermore, we analyze the challenges in current studies and propose key research directions for future work.